May Neutrophil-Lymphocyte and Platelet-Lymphocyte Ratios Indicate Disease Activity in Ankylosing Spondylitis? - Esra ERKOL İNAL,; İsmihan SUNAR,; Şadiye SARATAŞ,; Pınar EROĞLU,; Salih İNAL,; Mahmut YENER1, (Archives of Rheumatology, 2015)
Objectives: This study aims to evaluate the associations between neutrophil-lymphocyte ratio (NLR), mean platelet volume, and platelet lymphocyte ratio (PLR) with disease activity in ankylosing spondylitis. Patients and methods: The study included 103 patients (63 males, 40 females; mean age 40.7±12.0 years; range 20 to 70 years) with ankylosing spondylitis and 70 healthy controls (43 males, 27 females; mean age 42.7±15.3 years; range 18 to 66 years). All participants’ age, sex, erythrocyte sedimentation rate, C-reactive protein and mean platelet volume levels, total white blood cell, neutrophil, lymphocyte, and platelet counts were recorded while patients’ Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Functional Index and Bath Ankylosing Spondylitis Metrology Index scores, medication types, duration of disease and medication use were recorded. Patients were divided into three groups: healthy controls (group 1), patients having BASDAI scores <4 with mild disease activity (group 2, n=73), and patients having BASDAI scores ≥4 with moderate-severe disease activity (group 3, n=30). NLR and PLR values were calculated. Results: Counts of neutrophil, NLR, C-reactive protein levels and PLR were significantly higher in group 3 compared to groups 1 and 2 (p<0.05). BASDAI scores were correlated weakly with neutrophil counts, NLR and PLR, and correlated moderately with C-reactive protein and erythrocyte sedimentation rate (p<0.05). Conclusion: Our study results indicate that, in ankylosing spondylitis, mean platelet volume is not associated with disease activity, whereas NLR and PLR may reflect disease activity.